Exploring men's attitudes to mental fitness through sportspeople's lived experience. (2nd November 2019) - Cooper, Sarah Elizabeth; Parry, Sarah; Livanou, Maria; Sculthorpe, Daniel
Abstract : An interpretative phenomenological analysis sought to explore how male audience members experienced listening to mental health nurses alongside sportspeople who shared their lived stories of mental health problems in public through mental fitness sessions carried out by the mental health charity, State of Mind Sport. Six male participants were interviewed about their experience after attending an mental fitness session. Three superordinate themes emerged: 'Evolving male openness about mental health' looks at how the male audience members' perspective on being open about their mental health changed having been to the mental fitness session. Second, 'Sportspeople's influence' reflects upon the positive influence sportspeople's involvement in the mental fitness sessions has on male audience members. Finally, 'The process of learning about mental health' explores the educational impact the sessions appear to be having. The results demonstrated the mental fitness sessions had a positive impact and using sportspeople can improve mental health interventions with males and this has potential implications for mental health nursing interventions.